Biology Students’ Questioning Behaviour in Relation to Their Achievement in Biology in Barkin Ladi, Local Government Area, Plateau State - Ezekiel, D. P.; Yilshik, , O. M.; Joseph, M. (Kashere Journal of Education, 2021)
This study investigated the relationship between senior secondary two students’ questioning behaviour and their achievement in Biology in Barkin Ladi Local Government Area of Plateau State. The research design was partly an ethnographic research design through observation and narrative survey. The study also incorporated a correlational research design in which the correlation coefficient was computed to determine the relationship between the variables. The population of the study comprised all the fifteen (15) senior secondary schools in Barkin Ladi. A sample of two senior secondary schools out of fifteen senior secondary schools was selected using a purposive sampling technique. Blooms’ category system was used to transcribe students’ questions. The research instruments were observation using Audiotape recorder and the Biology Achievement Test (BAT). The audiotape recorded students’ questions were coded by two science education specialists at the University of Jos, while the test items were also scrutinized by two biology teachers at the secondary school level. The reliability of the BAT was determined using the split half method and it yielded 0.80. The research questions were answered using descriptive statistics while Pearson Product Moment Correlation was used in testing the Null hypothesis at the 0.05 level of significant. The findings indicated that a high positive linear relationship exists between the raw number of students’ questions and their achievement scores in Biology. The findings equally showed that students asked mostly low level questions and the types of questions that students ask during biology lesson does not depend on gender. Consequently, the study recommended among other things, the training and retraining of teachers as well as students on how to ask thought provoking questions to facilitate students’ performance, teaching and learning of Biology in Senior Secondary schools.